2020
DOI: 10.1016/j.jaccas.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

SAM and Severe Mitral Regurgitation Post–Acute Type A Aortic Dissection Surgery Treated With MitraClip

Abstract: Post-operative systolic anterior motion associated with mitral regurgitation can be a challenging combination. We present the case of a 64-year-old male patient managed by MitraClip (Abbott Laboratories, Abbott Park, Illinois) implantation for systolic anterior motion and severe mitral regurgitation in the early post-operative period after aortic dissection surgery. This is the first description of MitraClip use post–aortic dissection. ( Level of Difficulty: Intermediate. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, this is the first reported case successfully treated with MitraClip for chronic severe mitral regurgitation after surgery for type A aortic dissection combined with Marfan syndrome. In addition, previous case reports demonstrated that MitraClip was also effective in individuals with postacute type A aortic dissection surgery and Marfan syndrome 11,12 . This shows that MitraClip could be a viable option for these high‐risk patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first reported case successfully treated with MitraClip for chronic severe mitral regurgitation after surgery for type A aortic dissection combined with Marfan syndrome. In addition, previous case reports demonstrated that MitraClip was also effective in individuals with postacute type A aortic dissection surgery and Marfan syndrome 11,12 . This shows that MitraClip could be a viable option for these high‐risk patients.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, previous case reports demonstrated that MitraClip was also effective in individuals with postacute type A aortic dissection surgery and Marfan syndrome. 11,12 This shows that MitraClip could be a viable option for these high-risk patients.…”
mentioning
confidence: 96%
“…Recently, Tagliari et al 4 have published an interesting case report of MitraClip implantation for systolic anterior motion and severe MR in the early postoperative period after aortic dissection surgery. Although this case shares some similarities with ours, a main difference has to be outlined: our patient had no record of mitral valve disease preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic anterior motion (SAM) of the mitral valve is a cardiac functional disorder that can be induced by multifactorial dynamic components, such as left ventricular (LV) structures, mitral valvular or subvalvular structures, and patients' cardiovascular hemodynamics [1][2][3][4]. Preventing SAM is important, because once SAM occurs, the hemodynamics may be unstable, leading to a critical situation [5]. Here, we present a rare case of a patient with unstable SAM associated with acute type A aortic dissection (AAD) who underwent a one-step surgery for ascending aortic replacement and concomitant interventricular septal myectomy (IVSM) for the treatment of SAM.…”
Section: Introductionmentioning
confidence: 99%